Using Excel for business analysis a guide to financial modelling fundamentals - Fairhurst, Danielle Stein (Wiley, 2015)
Utilize Excel 2013 capabilities to build effective financial models Using Excel for Business Analysis, Revised Edition provides practical guidance for anyone looking to build financial models. Whether for business proposals, opportunity evaluation, financial reports, or any other business finance application, this book shows you how to design, create, and test your model, then present your results effectively using Excel 2013. The book opens with a general guide to financial modeling, with each subsequent chapter building skill upon skill until you have a real, working model of your own. Fina.
Includes index. - Includes bibliographical references and index. - Online resource; title from PDF title page (John Wiley, viewed April 21, 2015)
Keywords: Microsoft Excel (Computer file); Corporations -- Finance; Corporations -- Finance -- Computer programs; Microsoft Excel (Fitxer informàtic); Corporations; Finance; Corporations; Finance; Computer programs; Societats; Finances; Llibres electrònics